Amniotic membrane use for management of corneal limbal stem cell deficiency. Issue 4 (July 2017) - Sabater, Alfonso L.; Perez, Victor L.
Abstract : Purpose of review: The current article reviews the most recent surgical techniques for management of corneal limbal stem cell deficiency (LSCD) using amniotic membrane tissue. Recent findings: Early successes with amniotic membrane transplantation (AMT) for the treatment of ocular surface disorders have encouraged clinicians to investigate new applications. The use of AMT as a temporary patch in emergency cases in which LSCD may develop has considerably improved the prognosis of these patients. Amniotic membrane does not have stem cells of its own, but it supports regeneration of limbal epithelial stem cells (LESCs). Similarly, the combination of AMT with classic surgical techniques has enhanced the surgical success rates in most case series. Furthermore, based on its advantageous properties as a cell carrier, new applications to support in-vivo and ex-vivo cell expansion have been reported recently. Summary: LSCD constitutes a general indication for AMT. Based on the clinical scenario, AMT may be performed alone to support regeneration of LESCs, in combination with other surgical techniques, or even supporting the in-vivo or ex-vivo expansion of LESCs.